2020
DOI: 10.1002/anie.202007184
|View full text |Cite
|
Sign up to set email alerts
|

In‐Cell NMR Spectroscopy of Functional Riboswitch Aptamers in Eukaryotic Cells

Abstract: We report here the in-cell NMR-spectroscopic observation of the binding of the cognate ligand 2'-deoxyguanosine to the aptamer domain of the bacterial 2'-deoxyguanosine-sensing riboswitch in eukaryotic cells,n amely Xenopus laevis oocytes and in human HeLa cells.T he riboswitch is sufficiently stable in both cell types to allow for detection of binding of the ligand to the riboswitch. Most importantly,w e show that the binding mode established by in vitro characterization of this prokaryotic riboswitch is main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 46 publications
0
39
0
Order By: Relevance
“…This unique methodology relies on the high sensitivity of the chemical shift of the nuclear spins to the chemical surroundings to provide information at atomic resolution on the conformation, dynamics and interactions of a macromolecule in its physiologically relevant environment. In recent years, several examples of in-cell solution NMR both in bacterial and eukaryotic cells have demonstrated that, albeit challenging, the methodology can be applied to study protein structure (Sakakibara et al 2009;Tanaka et al 2019), conformation of nucleic acids (Dzatko et al 2018;Broft et al 2020), folding and maturation (Banci et al 2013;Luchinat et al 2014;Capper et al 2018), effects of the environment on protein stability and compactness (Majumder et al 2015;Smith et al 2016;Theillet et al 2016), chemical modifications (Binolfi et al 2016;Mercatelli et al 2016;Polykretis et al 2019), and protein-drug interactions (DeMott et al 2018;Luchinat et al 2020a). Furthermore, time-resolved in-cell NMR is increasingly applied to observe intracellular events in real time through the use of NMR bioreactors to keep cells alive for longer periods of time (Sharaf et al 2010;Kubo et al 2013;Breindel et al 2018;Cerofolini et al 2019;Luchinat et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…This unique methodology relies on the high sensitivity of the chemical shift of the nuclear spins to the chemical surroundings to provide information at atomic resolution on the conformation, dynamics and interactions of a macromolecule in its physiologically relevant environment. In recent years, several examples of in-cell solution NMR both in bacterial and eukaryotic cells have demonstrated that, albeit challenging, the methodology can be applied to study protein structure (Sakakibara et al 2009;Tanaka et al 2019), conformation of nucleic acids (Dzatko et al 2018;Broft et al 2020), folding and maturation (Banci et al 2013;Luchinat et al 2014;Capper et al 2018), effects of the environment on protein stability and compactness (Majumder et al 2015;Smith et al 2016;Theillet et al 2016), chemical modifications (Binolfi et al 2016;Mercatelli et al 2016;Polykretis et al 2019), and protein-drug interactions (DeMott et al 2018;Luchinat et al 2020a). Furthermore, time-resolved in-cell NMR is increasingly applied to observe intracellular events in real time through the use of NMR bioreactors to keep cells alive for longer periods of time (Sharaf et al 2010;Kubo et al 2013;Breindel et al 2018;Cerofolini et al 2019;Luchinat et al 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the method is not limited to transiently transfected human cells and should be applicable to cells where isotope-labeled proteins are delivered through electroporation (Bekei, 2013;Theillet et al, 2016) or other techniques (Inomata et al, 2009;Ogino et al, 2009), as well as to protein expressed in insect cells (Hamatsu et al, 2013) and bacterial cells (DeMott et al, 2018;Siegal & Selenko, 2019). In addition to protein targets, ligand affinity towards other types of targets, such as DNA and RNA, can also be investigated (Krafcikova et al, 2019;Broft et al, 2021). Furthermore, with a more complete characterization of the intracellular binding kinetics of the reference compound, competition binding/unbinding curves obtained by real-time bioreactor in-cell NMR could be fitted according to the drugtarget residence-time model (Copeland, 2016), which considers the lifetime of the drug-target complex as a more reliable parameter for assessing drug potency in cells and tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past ten years, in-cell spectroscopic methods, in particular, in-cell nuclear magnetic resonance (NMR), electron paramagnetic resonance (EPR), and Förster resonance energy transfer (FRET), have emerged as an efficient and viable alternative to the characterization of NA structures and interactions in the artificial conditions of buffers [ 8 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. These methods allow the quantitative description under physiologically relevant conditions, i.e., in living cells.…”
Section: Introductionmentioning
confidence: 99%
“…In 2018, two distinct groups adopted the in-cell NMR approach to characterize the structure of NAs in living human cells [ 25 , 42 ]. The approaches have proven helpful for validating DNA target structure in vivo [ 30 , 42 , 43 , 44 ] and for a semi-quantitative characterization of the ligand binding to double-stranded (ds)DNA and RNA aptamers [ 8 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation